RULA BASKET (SEAWEED BASKET): THE UTILIZATION OF RECYCLED PLASTIC WASTE TO BE CREATED ECONOMIC VALUE PRODUCT - Pratiwi, Rifqah; Amalo, Pieter; Dian Kusuma, Ni Putu; Serihollo, Lukas G.G (Management Science Research Journal, 2023)
The utilization of plastic waste can lead to innovation the support of economy and creativity peoples. The upcycling of plastic cup waste into handicraft supplies is one of the solutions to minimalize plastic cup waste around the coast. The making of Rula Basket is aimed to change the people’s mindset on how to make use of waste plastic cups into an alternative to seaweed basket that is made of rattan, as well as to create a positive activity for women’s empowerment in the coastal area. The research methods used Descriptive analysis. Developing Rula Basket is expected to be one of the women empowerment ventures to increase the economy by recycling plastic cup waste into appropriate products with economic value. This measure was also carried out to preserve the aquatic ecosystem in Tablolong Beach, Tablolong Village, West Kupang, East Nusa Tenggara.